7-(-2-g)=-4

Simple and best practice solution for 7-(-2-g)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-(-2-g)=-4 equation:


Simplifying
7 + -1(-2 + -1g) = -4
7 + (-2 * -1 + -1g * -1) = -4
7 + (2 + 1g) = -4

Combine like terms: 7 + 2 = 9
9 + 1g = -4

Solving
9 + 1g = -4

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 1g = -4 + -9

Combine like terms: 9 + -9 = 0
0 + 1g = -4 + -9
1g = -4 + -9

Combine like terms: -4 + -9 = -13
1g = -13

Divide each side by '1'.
g = -13

Simplifying
g = -13

See similar equations:

| 12+3b=4(3+6b) | | a^3*a^0= | | -7d+10=-3d-10-4 | | 3*1/7 | | 3(5p-15)=-20 | | 2|x+3|-4=-6 | | h+h+h= | | 6y+2(y+3)=2 | | (x-3)(x+8)(x-5)=360 | | (6/11)*(6/11) | | 8+1.7x=9 | | 30k+100=2k+120 | | X-6(6-x)=4-x | | -4f+7=-5f | | 3/4x+2=7 | | 15=2x+75 | | 10(9+2n)= | | X+26+6=3x+6 | | d=2/3c | | 3/5k=2 | | -4/7*9 | | a=6(a+4) | | 4x+3x-10=11 | | 2(5f+9)= | | 3w^2-6w=24 | | (4/(3b-2))-(7/(3b+2)) | | (-7/11)*(2/5) | | 4x+8-7x=-22 | | 5+5b=5(1+5b) | | m=9+10m | | M/6-1=6 | | 7n-7=5n+7 |

Equations solver categories